Confronting institutional boundaries to public participation: a case of the Danish energy sector. Issue 4 (3rd April 2019) - Nielsen, Helle Nedergaard; Aaen, Sara Bjørn; Lyhne, Ivar; Cashmore, Matthew
ABSTRACT: Although public participation has become an integrated part of planning practice, experience and documents literature still document difficulties in implementing participatory planning processes that provide arenas where citizens can truly influence planning. Based on a combination of institutional theory and action research methodology, this paper focuses on the institutional boundaries to introducing participatory practices by exploring openings and closures to the adoption of participatory planning processes by the Danish energy transmission system operator (TSO). Public participation in the Danish energy sector is characterized by complex institutional arrangements. The study shows how institutional boundaries are perceived by planners and how openings and closures can be identified and developed in an action research approach. The study reveals that citizen involvement has the potential to influence existing power structures but is highly challenged by an instrumentialised and sector-divided planning.